PENGARUH PENGELOLAAN KEUANGAN DAN PENGAWASAN KEUANGAN TERHADAP KINERJA ORGANISASI PERANGKAT DAERAH DI PROVINSI BENGKULU - Afri Darmawan; Nila Aprilla (UNIB Press, 2023)
The objective of this study was to prove the influence of the administration of financial statement and financial control on the performance of Local Government Organization at the Bengkulu Province. The data used in this study was primary data obtained from the distribution of questionnaires to the financial managers of Local Government Organization at the Bengkulu Province. The number of samples used in this study was 108 peoples. However, from the result of the distribution of questionnaires, it was found that the number of samples that was feasible to be analyzed was only 96 peoples. The method of data analysis used was descriptive analysis and multiple regression analysis. The obtained results of the study were: (1) the administration of financial statement has a significant influence on the performance of local government organizations in the Bengkulu Province and (2) the financial control has significant influence on the performance of local government organizations in the Bengkulu Province.